Ground elevation models and land cover classifers for decimetre resolution urban monitoring - Hingee, Kassel Liam (Curtin University, 2013)
This thesis presents methods that enable the generation of quantitative environmental indicators for remotely monitoring urban regions. Its contributions are a new morphological and surface fitting hybrid algorithm for the generation of ground elevation models, a vegetation classifier and significant research into Canonical Variate Analysis with Rational Polynomials (a feature extraction method that normalises the topographic illumination effect). These methods were tested on a 9600 square kilometre, 20cm resolution dataset covering Perth.